Acoustical and mechanical optimization of Camellia Sinensis/Ananas Comosus/GFRP/Epoxy composites by TOPSIS & Weighted Aggregates Sum Product Assessment method. (2021) - Gokulkumar, S.; Thyla, P.R.; Sathish, S.; Karthi, N.; Prabhu, L.; Vignesh, P.; Vishnu, R.; Srikanth, K.; Prasath, S. Vishnu
Abstract: Composites compressed by Camellia Sinensis/Anana Comosus/GFRP are universally recognized as a stronger substitute for acoustic damping. The environmental consequences due to carcinogenic materials, including polyhydride, polyurethane (PU) foams, polyethylene (PE), etc., act as a starting point for the development of high strength/weight, biodegradable and corrosion-resistant natural products (natural fiber-based composites). In this investigation, a single-dimensional pineapple fiber is combined with GRPF and waste tea flakes with help of an epoxy binder. Five different specimens of varying weight percentages were analyzed. The optimization method (TOPSIS & WASPAS) optimizes input parameter of weight fraction percentage with six corresponding different output responses. The best-integrated weight fraction percentage to enhance acoustic absorption is selected as the optimal concoction for the manufacture of acoustic damping materials.